Stages of busi(-)ness and identity - Lightfoot, Geoff; Fournier, Valérie (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2002)
RésuméThis article explores how space gets mobilised in the performance of “family business”. The very concept of the “family business” collapses some deeply entrenched distinctions in Western modern societies, those between home and work, private and public, family life and business rationality, distinctions that are mapped over space through the creation of boundaries between work space and family space, home and office. The “family business”, especially when run from home, unsticks this ordered sense of space as familial images and business stages are collapsed. Our analysis of small family run boarding kennels focuses on the way space is used to frame different stages of action. In particular, we draw upon theatrical metaphors to explore the work that goes into the staging of identities and social relations. We first discuss the relationships between space, stages, performance and identity through a theatrical lens; we then draw upon material from our study of family run boarding kennels to explore how owner-managers use space as a malleable resource from which they carve out and assemble different stages to perform their business and themselves to different audiences. After going back into the theatre to discuss the role of stages in weaving together coherent stories in the family business or in drama, we close by exploring the limitations of the theatrical metaphor for the analysis of social life.